Effects of chemotherapy on the musculoskeletal system in children and adolescents with acute lymphoblastic leukemia - Rodríguez Reyes, María Cristina; Galván Canchila, Diana Marcela (Universidad y Salud, 2014)
The purpose of this review is to determine the impact of chemotherapy on the musculoskeletal system in children and adolescents with Acute Lymphoblastic Leukemia (ALL). Relevant studies were identified in the databases PubMed, LILACS, Elsevier and ScieLO, combining the following search terms: lymphoblastic leukemia, children, osteonecrosis and late effects. Thirty- three articles published between 2002 and 2012 were considered. More available literature was found on complications in the administration of corticosteroids, being osteonecrosis the main consequence of chemotherapy on the musculoskeletal system.